A popular history of France - from the earliest times (1870) (14594455230) - Guizot | M. (François)... (Wikimedia Commons, 1870)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons; Iconographie